Impact of machine stiffness on ''pop-in'' crack propagation instabilities. (15th October 2018) - Petit, Tom; Ritter, Claire; Besson, Jacques; Morgeneyer, Thilo F.
Graphical abstract: Highlights: The decrease of tearing modulus causes appearance of pop-ins. The decrease of system stiffness causes appearance of pop-ins. An instability criterion using J-integral is established for CT samples. A dedicated device to change machine stiffness is set in place. Interaction between tearing modulus and system stiffness causes instabilities. Abstract: This study investigates ''pop-in'' phenomenon, i.e. unstable but limited crack propagation associated with a sudden decrease in load. Its origin is linked to an interaction between material tearing modulus and machine stiffness. Small scale yielding criterion for instability is applied to compact tension (CT) samples. To validate this criterion experimentally, firstly tests are performed on aluminum alloy with various tearing moduli. Secondly the effect of mechanical loading on pop-in behavior is studied by varying machine stiffness using an innovative setup. Pop-ins are shown to be mechanical instabilities due to interaction between material tearing modulus and system stiffness.